CCR3 Is Associated with the Death of a Photoreceptor Cell-line Induced by Light Exposure - Kuse, Yoshiki; Tsuruma, Kazuhiro; Kanno, Yusuke; Shimazawa, Masamitsu; Hara, Hideaki (Frontiers in Pharmacology, 2017)
The C-C chemokine receptor type 3 (CCR3) is the receptor for eotaxins (CCL-11, 24, 26), RANTES (CCL-5) and MCP-3 (CCL-7). It was reported that an inhibition of CCR3 by antagonists or antibodies reduces the degree of laser-induced choroidal neovascularization in mice, a model for wet age-related macular degeneration (AMD). Although several chemokine receptors have the potential of reducing the degree of the chronic inflammation in experimental dry AMD, the association of CCR3 remains unknown. The purpose of this study was to determine the role played by CCR3 in the death of 661W cells which are cells of a murine photoreceptor-derived cell line as an in vitro model of dry AMD. The expression of CCR3 was increased in the 661W cells after light exposure. Inhibition of CCR3 reduced the rate of cell death induced by light exposure. A blockade of CCR3 signaling by CCR3 silencing and two kinds of CCR3 antagonists, SB 328437 and SB 297006, reduced the rate of light-induced cell death. In addition, CCR3 inhibition decreased the level of reactive oxygen species and the activation of caspase-3/7 induced by light exposure. These findings indicated that the CCR3 blockade should be considered for the treatment of the dry AMD.